Identification of HSPD1 as a novel invasive biomarker associated with mitophagy in pituitary adenomas - Yu Zhang; Xin Ma; Congyu Liu; Zhixu Bie; Gemingtian Liu; Pinan Liu; Zhijun Yang (Translational Oncology, 2024)
Background: The crucial role of mitophagy in tumor progression has been recognized. Therefore, our study aimed to investigate the potential correlation between pituitary adenoma invasiveness and the mitophagy processes. Methods: In this study, we used transcriptomics of postoperative tissue from 32 patients and quantitative proteomics of 19 patients to screen for mitophagy-related invasion genes in pituitary adenomas. The invasive predictive value of target genes was analyzed by Lasso regression model, CytoHubba plugin and expression validation. Co-expression correlation analysis was used to identify paired proteins for target genes, and a predictive model for pituitary adenoma invasiveness was constructed by target genes and paired proteins and assessed using ROC analysis, calibration curves and DCA. GO function, pathway (GSEA or GSVA) and immune cell analysis (ssGSEA or CIBERSORT) were further utilized to explore the action mechanism of target gene. Finally, immunohistochemistry and cell function experiments were used to detect the differential expression and key roles of the target genes in pituitary adenomas. Results: Finally, Heat shock protein family D member 1 (HSPD1) was identified as a target gene. The quality of a predictive model for pituitary adenoma invasiveness consisting of HSPD1 and its paired protein expression profiles was satisfactory. Moreover, the expression of HSPD1 was significantly lower in invasive pituitary adenomas than in non-invasive pituitary adenomas. Downregulation of HSPD1 may be significantly related to invasion process, mitochondria-related pathway and immune cell regulation in pituitary adenomas. Conclusion: The downregulation of HSPD1 may serve as a predictive indicator for identifying invasive pituitary adenomas.